Pengaruh Media Kuis Interaktif Menggunakan Aplikasi Kahoot Terhadap Hasil Belajar Peserta Didik Pada Materi Sistem Ekskresi Manusia - Dini Andriani; Purwati Kuswarini Suprapto; Samuel Agus Triyanto (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
The development of information technology is increasing rapidly in the era of globalization, making educators required to adapt to technological developments, one of which is by learning interactive quizzes. This study aims to determine the interactive quiz media using the Kahoot application on student learning outcomes on the material of the human excretory system in Class XI MIPA SMAN 10 Tasikmalaya Academic Year 2021/2022. The research method uses a quasi-experimental research design with Nonequivalent Pretest-Posttest Control Group Design. The population in this study were all class XI MIPA SMAN 10 Tasikmalaya, as many as four classes totalling 141 students. The sampling technique used is purposive sampling, with the sample used class XI MIPA 2 as the experimental class and XI MIPA 3 as the control class with several students 71 people. The instrument used in this study was to measure student learning outcomes through a multiple-choice test of 30 questions referring to indicators C1, C2, C3, C4, and C5. The data analysis technique used is the independent t-test. The results showed a significant effect of the interactive quiz method using the Kahoot application on student learning outcomes with a significance value (of 0.002). These positive results can be used as a reference for educators to use Kahoot in supporting teaching and learning activities